The Impact of Green Brand Elements on Consumer Loyalty for Green Cosmetics After COVID 19 Outbreak in Malaysia - Iqbal, Jaweria (Curtin University, 2023)
The findings of this study suggest that Green Brand Elements have significant positive impact on the consumer loyalty for green cosmetics after the outbreak of COVID-19 in Malaysia. The study offers an appropriate perspective for fresh ideas in green marketing in line with environmental trends, initiatives, and favorable brand perception to enhance consumers' confidence to use green cosmetics. Therefore, this study directly benefits the cosmetics industry of Malaysia and the overall global green economy.